IMPLEMENTASI PEMBELAJARAN PAI DALAM MEMBENTUK KARAKTER ISLAMI SISWA DI SMA IT AL-HIJRAH II - Asti Indah Lestari Nst; Zaini Dahlan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of Islamic Religious Education (PAI) in shaping Islamic character among students at SMA IT Al-Hijrah II. The research focuses on the teacher’s strategies in PAI learning, the role of teacher exemplarity and religious school programs in strengthening character development, and the challenges faced in the digital era. This research employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation. The subjects include an Islamic Education teacher, the school principal, and four students. The results show that the implementation of PAI learning at SMA IT Al-Hijrah II has been effectively carried out through three main stages: transfer of knowledge (delivery of religious knowledge), transfer of values (internalization of Islamic values), and transfer of practice (application of Islamic principles in daily life). The PAI teacher plays a key role in developing students’ Islamic character through contextual learning strategies, religious habituation, and exemplary conduct. Religious programs such as Bina Pribadi Islami (BPI), MABIT, Mutabaah Amal Yaumiyah, and Tahfiz Al- Qur’an further strengthen the moral and spiritual formation of students. The main challenges in implementing PAI in the digital era include the negative influence of social media, decreased motivation for worship, and limited supervision outside the school environment. The school and teachers address these challenges through continuous spiritual guidance, collaboration with parents, and the use of digital media as educational tools for Islamic propagation. Therefore, the implementation of PAI at SMA IT Al-Hijrah II significantly contributes to fostering Islamic character, reflected in students’ religious, disciplined, and responsible behavior in everyday life.